Evaluation of the Hospital Information System (HIS ) using EUCS and PIECES Methods on the Medical Record Section of RSUD dr. Haryoto Lumajang - Hanesya, Arini Farihatul; Novi Marchianti, Ancah Caesarina; Bukhori, Saiful (International Journal of Computer, Network Security and Information System, 2021)
The use of HIS itself in Indonesia is 82.21% of hospitals have adopted HIS and only 15.79% have not adopted HIS. However, the use of SIMRS still uses paperless medical records because there are still several aspects of SIMRS that need to be developed according to user needs. The purpose of this study was to evaluate HIS using the PIECES and EUSC methods. The PIECES method is used to evaluate based on system performance consisting of performance, information, economy, control, efficiency and service variables. The EUSC method is used to evaluate user satisfaction using content, format, acurancy, timeliness and easy of use variables. This type of research is quantitative descriptive and analytic with a sample of 45 people. Descriptive data processing using scoring and analytical using chi square test. Descriptive data processing using scoring and analytical using chi square test. The results of descriptive research using the PIECES method: the performance variable is 69.0%, the information variable is 70.18%, the economy variable is 67.3%, the control variable is 71.4%, the efficiency variable is 72.3%, the service variable is 73. ,2% and all variables included in the good category. The results of analytical research using the End User Computing Satisfaction method found that there are 4 variables that affect user satisfaction, namely content, format, timeliness and easy of use, while the acurancy variable does not affect HIS user satisfaction.